Cost effectiveness analysis of laparoscopic hysterectomy compared with standard hysterectomy: results from a randomised trial. Issue 7432 (7th January 2004) - Sculpher, Mark; Manca, Andrea; Abbott, Jason; Fountain, Jayne; Mason, Su; Garry, Ray
Abstract : Objective To assess the cost effectiveness of laparoscopic hysterectomy compared with conventional hysterectomy (abdominal or vaginal). Design Cost effectiveness analysis based on two parallel trials: laparoscopic (n = 324) compared with vaginal hysterectomy (n = 163); and laparoscopic (n = 573) compared with abdominal hysterectomy (n = 286). Participants 1346 women requiring a hysterectomy for reasons other than malignancy. Main outcome measure One year costs estimated from NHS perspective. Health outcomes expressed in terms of QALYs based on women's responses to the EQ-5D at baseline and at three points during up to 52 weeks' follow up. Results Laparoscopic hysterectomy cost an average of £401 ($708; €571) more (95% confidence interval £271 to £542) than vaginal hysterectomy but produced little difference in mean QALYs (0.0015, -0.015 to 0.018). Mean differences in cost and QALYs generated an incremental cost per QALY gained of £267 333 ($471 789; €380 437). The probability that laparoscopic hysterectomy is cost effective was below 50% for a large range of values of willingness to pay for an additional QALY. Laparoscopic hysterectomy cost an average of £186 ($328; € 265) more than abdominal hysterectomy, although 95% confidence intervals crossed zero (-£26 to £375); there was little difference in mean QALYs (0.007, -0.008 to 0.023), resulting in an incremental cost per QALY gained of £26 571 ($46 893; €37 813). If the NHS is willing to pay £30 000 for an additional QALY, the probability that laparoscopic hysterectomy is cost effective is 56%. Conclusions Laparoscopic hysterectomy is not cost effective relative to vaginal hysterectomy. Its cost effectiveness relative to the abdominal procedure is finely balanced.